Determination of Freshwater Fish Types for Cultivation Based on Water Quality Using Mamdani Fuzzy: Penentuan Jenis Ikan Air Tawar untuk Budidaya Berdasarkan Kualitas Air Menggunakan Fuzzy Mamdani - Zayn, Afta Ramadhan; Al Farisi, Riswanda; Agung Nugroho, Benni; Heriadi, Agustono (Universitas Pesantren Tinggi Darul 'Ulum (Unipdu) Jombang, 2025)
Determining suitable fish species based on the available water quality in freshwater aquaculture is crucial. Selecting fish that are compatible with the existing water conditions can significantly influence their growth and survival, which in turn affects the overall harvest. Assessing water quality must therefore be done carefully and accurately, as each fish species has specific water requirements to reproduce and thrive optimally. In this study, a fuzzy logic approach using the Mamdani method was employed to assess the suitability of different freshwater fish species based on water quality conditions. The input parameters considered in the system include temperature, dissolved oxygen, and pH. Based on these parameters, the system categorizes the suitability of each fish species into three levels: suitable, moderately suitable, and less suitable for cultivation. The results of testing show that the system is capable of generating varying recommendations depending on the given water quality conditions. For instance, under conditions of 28°C temperature, 5 mg/L of dissolved oxygen, and pH 7, the system recommended catfish, pangasius, and eel as the most suitable species for cultivation. These recommendations can serve as a useful reference for aquaculture practitioners in selecting fish species that align with the environmental conditions of their farming locations.